2013
DOI: 10.1002/fuce.201300068
|View full text |Cite
|
Sign up to set email alerts
|

Modifying a Stainless Steel for PEMFC Bipolar Plates via Electrochemical Nitridation

Abstract: AISI446 stainless steel was electrochemically nitrided at room temperature. X‐ray photoelectron spectroscopy (XPS) analysis indicated that the nitrided steel was covered with surface ammonia and a layer of nitrides (mainly of mixed chromium nitrides). The nitride layer for 4 h nitrided steel at –0.9 V was about 2.5 nm thick. Dominating oxides appear on the steel's surface, so nitrogen incorporated oxides is a suitable term to describe the nitrided surface. The nitrided surface showed very low interfacial conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In a simulated PEMFC environment, nitrided 316 L stainless steel by electrochemical nitridation in nitrate-bearing solutions demonstrates exceptionally good electrochemical and corrosion properties . The nitrogen-incorporated oxides formed on the surface of stainless steel can effectively improve the corrosion resistance and electrical conductivity. ,− Although extensively investigated for PEMFC applications, the electrochemical nitridation technique has never been evaluated in Ti-based GDLs in PEM WE environments. Herein, for the first time, we focus on a method of electrochemical nitridation with a low-cost, corrosion-resistant, and conductive material for Ti-based GDLs in the PEM WE environment.…”
Section: Introductionmentioning
confidence: 99%
“…In a simulated PEMFC environment, nitrided 316 L stainless steel by electrochemical nitridation in nitrate-bearing solutions demonstrates exceptionally good electrochemical and corrosion properties . The nitrogen-incorporated oxides formed on the surface of stainless steel can effectively improve the corrosion resistance and electrical conductivity. ,− Although extensively investigated for PEMFC applications, the electrochemical nitridation technique has never been evaluated in Ti-based GDLs in PEM WE environments. Herein, for the first time, we focus on a method of electrochemical nitridation with a low-cost, corrosion-resistant, and conductive material for Ti-based GDLs in the PEM WE environment.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrate ions would adsorb on the metallic surface, being later reduced to NH 4 + and metal nitride. More recently, some authors have proposed the use of electrochemical nitriding to attain high corrosion resistance and conductivity for stainless steels employed as bipolar plates for polymer electrolyte membrane fuel cells (PEMFCs) [27][28][29]. The composition of the nitrided layer plays a major role in the corrosion behavior of the treated surface.…”
Section: Introductionmentioning
confidence: 99%
“…The composition of the nitrided layer plays a major role in the corrosion behavior of the treated surface. Wang et al [29] observed the formation of nitrogen incorporated oxide (oxi-nitrides) in the surface of electrochemically nitrided AISI 446 stainless steels.…”
Section: Introductionmentioning
confidence: 99%